2015
DOI: 10.4103/2277-9175.170240
|View full text |Cite
|
Sign up to set email alerts
|

Collagen cross-linking effect on progressive keratoconus in patients younger than 18 years of age: A clinical trial

Abstract: Background:Keratoconus is a bilateral non-inflammatory corneal disease. Collagen cross-linking (CXL) is a new treatment option for the disease that uses ultraviolet A light irradiation and riboflavin administration. The aim of this study is to evaluate the effect of CXL on corneal topographic and refractive values in patients with keratoconus younger than 18 years of age.Materials and Methods:For the clinical trial study, 37 patients (64 eyes) younger than 18 years of age with progressive keratoconus were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 25 publications
(29 reference statements)
1
21
0
Order By: Relevance
“…CXL achieves its effect through increased formation of crosslinks in the corneal stroma, thus enhancing corneal biomechanical stiffness [28]. In severe KC, the cornea is generally thinner and less biomechanically stable [29] compared with mild KC.…”
Section: Discussionmentioning
confidence: 99%
“…CXL achieves its effect through increased formation of crosslinks in the corneal stroma, thus enhancing corneal biomechanical stiffness [28]. In severe KC, the cornea is generally thinner and less biomechanically stable [29] compared with mild KC.…”
Section: Discussionmentioning
confidence: 99%
“…Riboflavin-assisted corneal collagen cross-linking is considered one of the most promising treatments in PK nowadays. [1011152021222324252627] The present study reports visual and morphological outcome in 78 eyes over a period of 1 year in a prospective setting of riboflavin-assisted C3R treatment. The results of the current study demonstrate statistically significant improvement in UCVA, BCVA, CS, K min , Sim K, spherical and cylinder power, and SE in the treatment group.…”
Section: Discussionmentioning
confidence: 99%
“…Similar observations with spontaneous clearing of stromal haze by the 3 rd month were reported by various authors. [10182023333435] Caporossi et al . [14] concluded that patients with advanced stage of keratoconus are at an increased risk of corneal haze which develops after C3R, with the causes being low corneal thickness and high corneal curvature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10] To date, however, no controlled trials have been performed to evaluate the efficacy or safety of CXL in children, although several cohort studies on crosslinking in pediatric populations have been published. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] In this study, we provide a systematic overview of the published literature regarding the outcome in children with progressive keratoconus who underwent CXL. In addition, we report the long-term outcome (ie, up to 5 yrs after undergoing CXL) of our own pediatric patient population, focusing on the efficacy and safety of CXL.…”
mentioning
confidence: 99%